If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1(r + 10) = r + -16 Reorder the terms: 1(10 + r) = r + -16 (10 * 1 + r * 1) = r + -16 (10 + 1r) = r + -16 Reorder the terms: 10 + 1r = -16 + r Solving 10 + 1r = -16 + r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-1r' to each side of the equation. 10 + 1r + -1r = -16 + r + -1r Combine like terms: 1r + -1r = 0 10 + 0 = -16 + r + -1r 10 = -16 + r + -1r Combine like terms: r + -1r = 0 10 = -16 + 0 10 = -16 Add '-10' to each side of the equation. 10 + -10 = -16 + -10 Combine like terms: 10 + -10 = 0 0 = -16 + -10 Combine like terms: -16 + -10 = -26 0 = -26 Simplifying 0 = -26 Combine like terms: 0 + 26 = 26 26 = -26 + 26 Combine like terms: -26 + 26 = 0 26 = 0 The solution to this equation could not be determined.
| -[6z-(14z+3)]=3+(7z+8) | | -9+4r=4r-9 | | 5-36x=-60 | | 8x^3-49x^2-49x=0 | | (3x+7)+(6x+20)=90 | | 3-2x=2+3x | | z^2+9z=7 | | f(-5)=1-4(-5) | | 5-36x=60 | | 2n+4n+12=-6 | | 0.15x=0.05x+40 | | y^2-9= | | 8(2)x+7y=184 | | 7-5x+8+2x+4x-3=17 | | x^2+21x+35= | | 3/4=a | | 2(2x-4)=6x-20 | | 8b+11-3b=z+8-2x | | 2(7x+2)+12(x+1)=2 | | x^3+7x^2-x=0 | | 9b=4c | | 2r^2+19r+42=0 | | 5x-15=85 | | 2p-9=5p+-2 | | x+4(x+1)=29 | | 4-(2x)=10-x | | 7.6x-3.7=-70.2 | | 12y-1+13=5y+2 | | 6x^2+6x-22=0 | | -36y-7+10=-8 | | (4x+15)+(3x+25)=180 | | -(5y-6)+4(3+5y)ify=2 |